2012
DOI: 10.1111/j.1464-410x.2011.10866.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of lower urinary tract symptoms in Japanese men from a 15‐year longitudinal community‐based study

Abstract: Abbreviations : PV , prostate volume ; Q max , peak urinary fl ow rate ; QoL , quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
(38 reference statements)
2
30
1
Order By: Relevance
“…Another important problem in geriatric urology is LUTS. In contrast to cancer, there are no racial differences in the incidence of LUTS . Recently, “frailty” has become a commonly used medical term in gerontology.…”
Section: Discussionmentioning
confidence: 99%
“…Another important problem in geriatric urology is LUTS. In contrast to cancer, there are no racial differences in the incidence of LUTS . Recently, “frailty” has become a commonly used medical term in gerontology.…”
Section: Discussionmentioning
confidence: 99%
“…From October 1992 to May 1993, we carried out a cross‐sectional community‐based study on sexual function as well as lower urinary tract symptoms in men aged 40–79 years in Shimamaki‐mura, Hokkaido, Japan . From February 2007 to February 2008, we also carried out the same cross‐sectional community‐based study, as in the initial survey . We compared the results of these two studies to determine longitudinal changes of their sexual function and sexual satisfaction.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we concluded that uroflowmetry can be used as an effective tool in MLUTS assessment of the patients. Most community-based studies showed that age and symptom scores showed a positive correlation (16)(17)(18)(19)(20) as well as an increase in LUTS severity with age. Despite some studies showing a negative correlation between age and symptom indexes (11,21), the majority of the studies including ours showed an increase in symptom scores with age.…”
Section: Discussionmentioning
confidence: 99%